FENOMENA KOMUNIKASI KELUARGA TNI ANGKATAN DARAT ASRAMA SAPTA MARGA IV KELURAHAN SARIO KOTABARU - Baramuli, Lidya Eunike Ibrahim (ACTA DIURNA KOMUNIKASI, 2013)
There are two types of acquiring messages in the house hold communication in National military of Indonesia. It is the democratic type and the authoritarian type. Both of the types are carried away by the a soldier families in spite of National military of Indonesia takes a role as a husband or father responsible to his wife and children. Keyword : household commuinication, democratic and authoritarian type